Calculati ;
√(-2)²+4(1-√27)+6 (√12-1)
Răspunsuri la întrebare
Răspuns de
1
√(-2)²+4(1-√27)+6 (√12-1) =
rad 4+4-4rad 27+6rad 12-6 =
2+4 -4*3rad3+6*2 rad 3-6 =
2+4-12 rad3+12 rad3-6 =
6-6 = 0
rad 4+4-4rad 27+6rad 12-6 =
2+4 -4*3rad3+6*2 rad 3-6 =
2+4-12 rad3+12 rad3-6 =
6-6 = 0
Răspuns de
0
2+4-12*3+12*3-6=6-6=0
( "*" E radical)
( "*" E radical)
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă
Biologie,
10 ani în urmă
rad 4+4-4rad 27+6rad 12-6 =
2-4*3rad3+6*2 rad 3-6 =
2-12 rad3+12 rad3-6 =
2-6 = -4